The Effect of Giving Date Palm Juice on the Duration of the First Stage of Labor in Sele Be Solu Hospital, Sorong City (Medico Legal Update, 2020)
The maternal mortality rate (MMR) in the world in 2017 is 216 per 100.00 live births and 99% of them aredue to childbirth problems in Indonesia. One of the causes of maternal mortality in Indonesia is prolongedlabor. The labor process requires optimal energy and stamina. One intake of energy/nutrition for childbirthis Date Palm juice, a mixture of 100 grams of dates with ± 200 cc of water blended using a blender. Thepurpose of this study was to determine the effect of dates palm juice on the duration of the first stage of laborin Sele Be Solu Hospital in Sorong City.The research design uses Quasy Experiment (quasi-experimental) with Non-equivalent Posttest OnlyControl Group. Time and place of research 20 May - 15 June 2019 at Sele Be Solu Regional Hospital,Sorong City. A sample of 32 respondents using purposive sampling technique. The independent variablewas giving of date palm juice and the dependent variable was the normal labor duration of the first stage oflabor. Data collection used observation sheets and partographs. Statistical analysis using Independent T-Testwith a significance level of 0.05. After giving date palm juice to the intervention group p-value = 0,000 ? =0.05 was obtained. There is an effect of Date Palm juice to facilitate normal labor duration of the first stageat Sele Be Solu Regional Hospital in Sorong City.